HUBUNGAN PERILAKU MASYARAKAT DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI PUSKESMAS TELING KOTA MANADO - Stefanus Timah (Yayasan Syalom Cipta Sumikolah, 2025)
Infectious diseases caused by viruses from the troubled Arbovirosis group A and B group in Indonesia are known as Dengue Hemorrhagic Fever (DHF) which is an endemic disease and causes health problems, not only in Indonesia but also in the tropical and subtropical regions of the world, Community Behavior relationship with DHF incidence in the work area of Teling Puskesmas Manado. The type of this research is descriptive analytic research with Cross Sectional study approach, time and place of research has been done in march year 2017 located in Puskesmas Teling Manado City. The population in this study is all people who suffer from dengue fever amounted to 30 respondents.Data analysis used in this research is univariate analysis and bivariate analysis for bivariate analysis in menanalisa relationship between variables then tested with Chi- Square with degree of confidence 95% if show significant relation, if show influence not meaningful. Conclution From the results of the study note that there is a significant relationship between knowledge with the incidence of dengue fever, there is a significant relationship between attitude with the incidence of dengue fever.